Complete nucleotide sequence of a unique HLA class I C locus product expressed on the human choriocarcinoma cell line BeWo. - Ellis, SA; Strachan, T; Palmer, MS; Mcmichael, A (1989)
We have used Northern blot analysis to detect mRNA from class I HLA genes in the human choriocarcinoma cell line BeWo, which has been previously shown to express an atypical HLA class I molecule, in the absence of HLA A and B. Hybridization was seen with three class I DNA probes, the strongest being seen with the probe pC800, which corresponds to an 800-bp section of the Cw3 gene. We have made cDNA libraries from BeWo cells and screened for positive clones by using class I DNA probes. Of the clones isolated, we determined the complete sequence of one and partial sequence of five shorter clones. They all code for an identical C locus-related product, which does not correspond to published C locus sequences.